THE CHOICE AND SUBSTANTIATION OF THE MATHEMATICAL MODEL OF ELECTRORETINOGRAM IN THE FORM OF LINEAR STOCHASTIC PROCESS - Dzubin, S. V.; Matsiuk, A. V.; Martsenko, S. V.; Pryimak, M. V. (International Journal of Computing, 2014)
The mathematical model of electroretinogram as a linear random process which takes into account the mechanism of eye retina biopotentials forming and is suitable for solving of the measuring and diagnosing problems is developed in the work. The approach is proposed, the method is developed and the statistics are given to estimate the kernel of the linear random process as electroretinogram model. The obtained results may be used in the applied research of eye diagnosis.